2020
DOI: 10.1021/acs.jmedchem.9b02076
|View full text |Cite
|
Sign up to set email alerts
|

Achieving In Vivo Target Depletion through the Discovery and Optimization of Benzimidazolone BCL6 Degraders

Abstract: Deregulation of the transcriptional repressor BCL6 enables tumorigenesis of germinal center B-cells, and hence BCL6 has been proposed as a therapeutic target for the treatment of diffuse large B-cell lymphoma (DLBCL). Herein we report the discovery of a series of benzimidazolone inhibitors of the protein–protein interaction between BCL6 and its co-repressors. A subset of these inhibitors were found to cause rapid degradation of BCL6, and optimization of pharmacokinetic properties led to the discovery of 5-((5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 26 publications
(56 reference statements)
1
87
0
Order By: Relevance
“…BI-3802, as well as structurally related bioavailable analogs 29 , have markedly increased activity against lymphoma cells compared to BI-3812 6 , which is likely due to the combined effects of inhibiting co-activator binding, sequestering BCL6 into foci, and degrading BCL6. It has been previously shown that inhibition of BCL6 or degradation by PROTACs results in insufficient inhibition of downstream targets and consequently only minor anti-proliferative effects 5 .…”
Section: Discussionmentioning
confidence: 99%
“…BI-3802, as well as structurally related bioavailable analogs 29 , have markedly increased activity against lymphoma cells compared to BI-3812 6 , which is likely due to the combined effects of inhibiting co-activator binding, sequestering BCL6 into foci, and degrading BCL6. It has been previously shown that inhibition of BCL6 or degradation by PROTACs results in insufficient inhibition of downstream targets and consequently only minor anti-proliferative effects 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The solventexposed moiety of BI-3812 clashes with a helix of BTBb. (C) Another inhibitor-degrader pair identified for BCL6 (Bellenie et al, 2020). (D) Inhibitor and degrader of BRD4 (Blake, 2019).…”
Section: Compound-induced Stickinessmentioning
confidence: 99%
“…Based on this concept, various synthetic inhibitors of BCL6-co-repressor interactions have been developed, all of which target the lateral groove (Cardenas et al, 2016;Cerchietti et al, 2009Cerchietti et al, , 2010Cheng et al, 2018;Evans et al, 2014;Ghetu et al, 2008;Kamada et al, 2017;Kerres et al, 2017;McCoull et al, 2017;Sakamoto et al, 2017;Silva et al, 2007;Yasui et al, 2017). Certain lateral groove-binding compounds induce the ubiquitin-dependent proteasomal degradation of BCL6 in the cell (Bellenie et al, 2020;Kerres et al, 2017;S1abicki et al, 2020) while others have been utilized as building blocks for proteolysis-targeting chimeras (PROTACs) (McCoull et al, 2018). Together, these studies highlight the remarkable susceptibility of the BTB fold to smallmolecule-mediated manipulations and the intriguing potential of harnessing this susceptibility for the therapeutic targeting of transcription factors.…”
Section: Introductionmentioning
confidence: 99%